2020
DOI: 10.3390/nu12113317
|View full text |Cite
|
Sign up to set email alerts
|

Cornus officinalis Ethanolic Extract with Potential Anti-Allergic, Anti-Inflammatory, and Antioxidant Activities

Abstract: Atopic dermatitis (AD) is an allergic and chronic inflammatory skin disease. The present study investigates the anti-allergic, antioxidant, and anti-inflammatory activities of the ethanolic extract of Cornus officinalis (COFE) for possible applications in the treatment of AD. COFE inhibits the release of β-hexosaminidase from RBL-2H3 cells sensitized with the dinitrophenyl-immunoglobulin E (IgE-DNP) antibody after stimulation with dinitrophenyl-human serum albumin (DNP-HSA) in a concentration-dependent manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…Among these natural compounds is cornelian cherry ( Cornus mas ) extract (CCE), which is composed of several active compounds, including five anthocyanins: delphinidin 3-galactoside, cyanidin 3-rhamnosylgalactoside, cyanidin 3-galactoside, pelargonidin 3-rhamnosylgalactoside, and pelargonidin 3-galactoside [ 12 ]. Ursolic acid is an important constituent of CCE [ 13 , 14 , 15 , 16 ] possessing antioxidant and antibacterial properties. Additionally, it contains vitamin C, trace minerals, organic acids, pectintriterpenoids, iridoids, pectins, and tannins that range within the safe standards levels of food [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these natural compounds is cornelian cherry ( Cornus mas ) extract (CCE), which is composed of several active compounds, including five anthocyanins: delphinidin 3-galactoside, cyanidin 3-rhamnosylgalactoside, cyanidin 3-galactoside, pelargonidin 3-rhamnosylgalactoside, and pelargonidin 3-galactoside [ 12 ]. Ursolic acid is an important constituent of CCE [ 13 , 14 , 15 , 16 ] possessing antioxidant and antibacterial properties. Additionally, it contains vitamin C, trace minerals, organic acids, pectintriterpenoids, iridoids, pectins, and tannins that range within the safe standards levels of food [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manu et al have indicated the beneficial effects of CO on type 2 diabetes, neuroinflammation, and bone loss [ 21 , 22 , 23 , 24 ]. Recent studies have shown that the CO extract possesses potent anti-inflammatory action against oxidative stress in RAW 264.7 cells and decreases proinflammatory factors, such as IL-1β, interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α), in numerous types of inflammation [ 25 , 26 , 27 ]. Additionally, aqueous extracts of the CO fruit reportedly inhibit OA symptoms in a testosterone-deficient mouse model [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pharmaceutical bioactive components derived from CO extract have been identified, including loganin, morroniside, caffeic acid, and ursolic acid [ 22 ]. Loganin, one of the most abundant compounds in CO extract, has been reported to be an anti-inflammatory agent by reducing reactive oxygen species and cytokines [ 23 , 24 ] and inhibiting inflammatory responses by attenuating NF-κB downstream signaling [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%